THE RISE OF DEGLOBALIZATION: IS THE WORLD MOVING AWAY FROM FREE TRADE? - Murodjon Sagdiddinov Rahimjonovich (Web of Journals Publishing, 2025)
The rise of deglobalization signals a crucial transformation in the international economy. This phenomenon of deglobalization presents a new challenge to international trade as it has existed since the mid-20th century. In this article, I attempt to analyze the broad question of whether deglobalization is just a phase or an enduring change. There has been a deglobalization movement marked by an increase in protectionism, and economic and environmental factors. The current evidence of trade, foreign direct investment, and the emergence of regional trade integration, such as RCEP, increases the scope of regions with lower economic growth rates and rising economic disparities. Deglobalization offers opportunities for less environmental damage and a decrease in income inequality on a global scale. However, it also has negative effects, such as promoting economic fragmentation and a decline in interdependence among nations. Therefore, there is a need for "smart globalization," which encourages a degree of self-reliance at the local level while also promoting global social interaction. This approach can help foster innovation, equity, and sustainable economic growth.
Keywords: Globalization, deglobalization, trade-to-GDP ratios, income inequality, supply chain disruptions, carbon tariffs, regional trade blocs, smart globalization.